Hodonymy of Chengdu and Yekaterinburg: a Comparative Aspect - E. E. Ivanova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The nominative types and models of the hodonyms of Chengdu and Yekaterinburg is compared in the article, the task of finding universals in the hodonymy is set. There are three main types of hodonyms: descriptive, memorial, and conventionally symbolic. Comparative analysis has shown that the descriptive type can be recognized as universal, since it most fully reflects the main function of the hodonyms: an indication of the location of the object and its characteristics. The authors note that this is the most ancient type for the spontaneously forming hodonymicon of any city. It has been proved that in Yekaterinburg in the Soviet era, descriptive hodonyms are supplanted by memorial ones, these are, first of all, names — dedications to memorable dates and milestones in national history, to specific persons associated with the history of the country and the city. It has been established that descriptive names remain the most widespread in Chengdu, and conventionally symbolic type hodonyms are also popular, among which names, including traditional symbols of Chinese culture, good wishes, as well as abstract concepts expressing various positive qualities predominate. It is emphasized in the article that the hodonyms of the memorial and conditionally symbolic type in Chengdu and Yekaterinburg are fundamentally different, being a reflection of the history and culture of their countries